Analysis of Needs Seen in “Finding Dory”: A Movie Directed by Andrew Stanton - Hilma, Melitia; Fitriana, Eka; Isnaini, Muhammad (Program Studi Pendidikan Bahasa Inggris, 2025)
This study examines the character development of Dory in the animated film